A Novel lncRNA, LINC00460, Affects Cell Proliferation and Apoptosis by Regulating KLF2 and CUL4A Expression in Colorectal Cancer - Yifan Lian; Changsheng Yan; Hongzhi Xu; Jiebin Yang; Yang Yu; Jing Zhou; Yongguo Shi; Jianlin Ren; Guozhong Ji; Keming Wang (Molecular Therapy: Nucleic Acids, 2018)
Emerging evidence has proven that long noncoding RNAs (lncRNAs) play important roles in human colorectal cancer (CRC) biology, although few lncRNAs have been characterized in CRC. Therefore, the functional significance of lncRNAs in the malignant progression of CRC still needs to be further explored. In this study, through analyzing TCGA RNA sequencing data and other publicly available microarray data, we found a novel lncRNA, LINC00460, whose expression was significantly upregulated in CRC tissues compared to adjacent normal tissues. Consistently, real-time qPCR results also verified that LINC00460 was overexpressed in CRC tissues and cells. Furthermore, high LINC00460 expression levels in CRC specimens were correlated with larger tumor size, advanced tumor stage, lymph node metastasis and shorter overall survival. In vitro and in vivo assays of LINC00460 alterations revealed a complex integrated phenotype affecting cell growth and apoptosis. Mechanistically, LINC00460 repressed Krüppel-like factor 2 (KLF2) transcription by binding to enhancer of zeste homolog 2 (EZH2). LINC00460 also functioned as a molecular sponge for miR-149-5p, antagonizing its ability to repress cullin 4A (CUL4A) protein translation. Taken together, our findings support a model in which the LINC00460/EZH2/KLF2 and LINC00460/miR-149-5p/CUL4A crosstalk serve as critical effectors in CRC tumorigenesis and progression, suggesting new therapeutic directions in CRC. Keywords: LINC00460, KLF2, CUL4A, proliferation, apoptosis, colorectal cancer